Analysis on Students’ Interest in Speaking Skill (A Descriptive Quantitative to the Eleventh Grade Students of SMAN 1 Boyan Tanjung in the Academic Year of 2021/2022) - Wahyuni, Marisa Elentri; Kurniawati, Tri; Sahrawi, Sahrawi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2021)
The purposes of the research here 1) To find out the level of students’ interest in speaking skill at eleventh grade of SMAN 1 Boyan Tanjung. 2) To find out students' responses in speaking skill at eleventh grade in SMAN 1 Boyan Tanjung. The research method used in this research was descriptive method. Data collection techniques used in this research resume are Direct communication technique, and Indirect Communication Techniques. Data collection tools are questionnaires and interviews. The data analysis technique used is the formula percentage by Zuldafrial (2012:226). Based on the results of the study can be concluded that in that in a manner general speaking skill at Eleventh Grade in SMAN 1 Boyan Tanjung has been low interest. More specifically can be described as follows 1) The level of students’ interest in speaking skill at eleventh grade SMAN 1 Boyan Tanjung in the Academic Year of 2021/2022 which has a fairly good level of interest this is evident from the results of the acquisition of 50% included inpretty high category. 2) Students' responses in speaking skill at Eleventh Grade in SMAN 1 Boyan Tanjung in the Academic Year of 2021/2022 is low. The low interest of students in speaking English there are several factors from them not liking English, from accuracy, fear of spelling mistakes to difficult lessons for them.